ANALISIS STUDI KELAYAKAN BISNIS PADA PETERNAKAN BURUNG PUYUH DI KOTA PANGKALPINANG - Sapira, Meisye; Astuti, Nelly; Maharani, Yunita (Jurnal Ilmiah Niaga Bisnis Elektronik, 2021)
This thesis research entitled in Indonesian: “Analisis Studi Kelayakan Bisnis Peternakan Burung Telur Puyuh di Pangkalpinang" regarding feasibility study of Mrs. Maymuna's Quail Farm business is a business established with capital own capital, which is Rp 24,276,000,- investment capital and Rp 78,400.00,- operational capital in 1 period. The sales products produced by quail breeding are quail eggs and quail droppings. This study aims to determine the Market and Marketing Aspects, Aspects of Technical and technology, and financial aspects in Maymuna's mother quail farm which is located at JL. Parit Lalang, Rangkui Village, Pangkalpinang City. This research was carried out from February to June 2021 with data collection techniques in the form of observations and interviews. The method used is Aspect Market and Marketing, Technical and Technological Aspects, and Financial Aspect. Market and Marketing analysis shows that the prospect of Mrs. Maymuna's farm is quite good, this can be seen from the increase in the number of requests every year. Quality production at an affordable price, and a fairly good strategy related to the marketing mix.Technical and Technological analysis shows that the condition of the location and production equipment is clean and quality maintained, and meets production capacity. Based on the calculations of the five types of investment assessments, it is obtained that the financial aspects are reviewed from four types of investment assessments, namely Payback Period (PP),which is 10 months, the Net Present Value (NPV) is 124% -, the value of the Average Rate of Return (ARR) is Rp.1.070.442.412%, greater than 100%. Profitability Index (PI) That is Rp. 8.12801392.